Assessing health science students’ gaming experience: a cross-sectional study - Rodríguez-Roca, Beatriz; Calatayud, Estela; Gomez-Soria, Isabel; Marcén-Román, Yolanda; Cuenca-Zaldivar, Juan Nicolas; Andrade-Gómez, Elena; Subirón-Valera, Ana Belén (Frontiers in Education, 2023)
Background: Digital gamification in university students of degrees related to health is considered an innovative and beneficial tool complementary to traditional teaching.Objectives: to analyze the enjoyment experience obtained by university students from the Faculty of Health Sciences and to know the gender differences after participating in a digital game.Participants: A total of 156 university students from the Faculty of Health Sciences of the University of Zaragoza.The activity of a digital game took place in the 2021-2022 academic year and was carried out as a teaching innovation project with the final approval of the University of Zaragoza. The tools used were the Spanish version of the Gameful Experience Scale and a self-administered questionnaire on satisfaction and suitability reported by the activity.Results: A total of 156 students participated with an age of 21.2±6.2 years. The average that reached a higher score was enjoyment (4±0.7) and the lowest score was obtained in the dimension on the absence of negative effects (1.5±0.9). Cronbach's alpha for the whole Gameful Experience Scale was 0.95. There are significant differences in three dimensions of the Gameful Experience Scale: male students enjoyed more than female students (p=0.05), enjoyed a greater sense of domination (p=0.01) and had fewer negative effects (p=0.0). In suitable, the highest items were its application to other subjects of the Degree (m 4.4; SD 0.5), motivation to face the study (m 4.1; SD 0.8) or help when remembering concepts (m 4.4; SD 0.5).Gender influences student satisfaction after carrying out a gamification activity, specifically after a digital game. The dimensions in which gender differences were found were fun, absence of negative effects, and dominance.